HISTOLOGICAL ANALYSIS OF THE TEMPORAL INFLUX OF IMMUNE CELLS INTO HEPATIC GRANULOMAS INDUCED BY TAENIA PISIFORMIS IN RABBITS - F.I. Flores-Pérez; M. Pérez-Martínez; A. Pérez-Torres; I. Camacho-Arroyo; M.L. Garduño-Millán; R. Ramírez-Aquino H. Jiménez-Cortez; C. Hallal-Calleros (Journal of Animal and Plant Sciences, 2018)
The objective of this study was to evaluate histologically the temporal influx of immune cells into hepatic granulomas in domestic rabbits infected with Taenia pisiformis eggs at 28, 77 and 90 days post-infection (dpi). Our study has focused on the histological description of lesions in the liver by T. pisiformis, quantification of macrophages, lymphocytes, and eosinophils and measured of the total area of granulomas. Histological differences among days post-infection were found, granulomas area was higher at 77 and 90 dpi compared to 28 dpi. Total lymphocytes increased in relation to the time post-infection. Macrophages were the most numerous cells at 28 and 77 dpi (109.49±5.2 and 56.12±3.69, respectively), though they diminished about 50% at 77 dpi. Eosinophils were scarce and their number decreased with the progress of time post-infection. Foamy macrophages were observed, which had not previously been referred for cestodiasis. It is concluded that the histological characteristics of liver granulomas induced by infection with T. pisiformis in rabbits and the influx of immune cells changed at different periods post-infection. This information is fundamental to know more deeply the histological organization of rabbit granulomas in relation to the influx of immune cells in experimental post-infection periods.
Keywords: Granulomas; liver; Taenia pisiformis; lymphocytes; macrophages; rabbit